RATIONAL USE OF ANTIBIOTICS DURING THE COVID-19 PANDEMIC: Antibiotics during COVID-19 - Milovanovic, Jovica; Jotić, Ana; Radin, Zorana; Cirkovic, Ivana (Srpski medicinski časopis Lekarske komore, 2021)
Introduction/Aim: The global COVID-19 pandemic has long been considered an emergency, with the number of cases growing exponentially, despite constant efforts to control the infection. Although the disease is caused by the SARS-CoV-2 virus, most patients are treated with antibiotic therapy. The long-term effects of such broad antibiotics use on antimicrobial resistance are still unknown and are a matter for concern. The aim of this paper is: to determine, based on the available literature, the impact of the COVID-19 pandemic on the use of antibiotics; to determine the global situation regarding antimicrobial resistance; to identify key areas where urgent changes are needed.Methods: A systematic review of the current literature on the use of antibiotics in COVID-19 treatment was conducted. The PubMed and MEDLINE databases were searched for papers published between March 2020 and September 2021.Results: Between 76.8% and 87.8% of patients with COVID-19 were treated with antibiotics. Antibiotics were less frequently prescribed to children, as compared to adults (38.5%, compared to 83.4%). The most  commonly administered antibiotics were fluoroquinolones (20.0%), macrolides (18.9%), β-lactam antibiotics (15.0%), and cephalosporins (15.0%). Self-medication with antibiotics to prevent and treat COVID-19 has been identified as one of the important factors contributing to antimicrobial resistance.Conclusion: The impact of COVID-19 on global antimicrobial resistance is still unknown and is likely to be unevenly distributed in the general population. Although various antibiotics have been used to treat patients with COVID-19, their role and the need for their application in the treatment of this infection remains to be determined. For now, there are no reliable data as to whether the use of antibiotics in COVID-19 cases without associated bacterial infections has any effect on the course of the disease and mortality.
Keywords: antibiotics; COVID-19; antimicrobial resistance; bacteria